RISK FACTORS OF PREECLAMPSIA WITH SEVERE FEATURES AND ITS COMPLICATIONS - Eka Suci Wulandari; Ernawati Ernawati; Djohar Nuswantoro (UNIVERSITAS AIRLANGGA, 2021)
Abstract.Background : The maternal mortality rate in Indonesia is dominated by preeclampsia as the second highest cause after bleeding. Several predictors can be categorized as risk factors that can be used to increase alertness in the care of pregnant women with severe preeclampsia to avoid complications. The purpose of this study was to study the relationship between risk factors for severe preeclampsia and its complications. Methods: This study used an observational analytic method with a case control design. The sampling technique is simple random sampling. The number of samples in this study were 80 samples, with 40 samples in each group. The case group was severe preeclampsia with one complication and the control group was severe preeclampsia without complications. Statistical analysis used was chi square and multiple logistic regression analysis. Results: The results showed that there was a significant relationship between age variables (p value = 0.001 < 0.05; OR = 5.318; CI = 2.118 – 13,356), BMI (p value = 0.002 < 0.05; OR = 6.000; CI = 1.958 – 18.384 ) and gestational age (p value = 0.039 < 0.05; OR = 2.636; CI = 1.040 – 6.685). Multiple logistic regression analysis showed that BMI (p = 0.003), age (p = 0.001) and gestational age (p = 0.048) were variables included in the final modeling of the regression analysis with the incidence of severe preeclampsia complications. Conclusion: BMI is the variable that has the strongest relationship with the incidence of severe preeclampsia complications.